2018
DOI: 10.1080/2162402x.2018.1434467
|View full text |Cite
|
Sign up to set email alerts
|

The role of Galectin-3 in modulating tumor growth and immunosuppression within the tumor microenvironment

Abstract: The efficacy of cancer immunotherapy is limited, in part, by the multitude of immunosuppressive mechanisms present within the tumor microenvironment (TME). Galectin-3 (Gal-3) is a lectin that contributes to TME immunosuppression and regulates diverse functions including cellular homeostasis and cancer biology. Increased Gal-3 expression during cancer progression augments tumor growth, invasiveness, metastatic potential, and immune suppression, which highlights the potential use of Gal-3 as a therapeutic target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
138
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(144 citation statements)
references
References 53 publications
5
138
0
1
Order By: Relevance
“…To the best of our knowledge, endostatin or GAL3BP have not been reported as markers for treatment efficacy during immunotherapy in melanoma or other cancers. However, a galectin 3 inhibitor, in combination with ipilimumab or PD‐1 inhibition, is being currently evaluated for the treatment of patients with metastatic melanoma underscoring that galectin 3 or its marker Gal3BP (as well as endostatin) could be part of a panel of biomarkers that predicts the outcome for immunotherapy in melanoma. Our data suggest endostatin and Gal3BP as potential prognostic biomarkers for ipilimumab in MM.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, endostatin or GAL3BP have not been reported as markers for treatment efficacy during immunotherapy in melanoma or other cancers. However, a galectin 3 inhibitor, in combination with ipilimumab or PD‐1 inhibition, is being currently evaluated for the treatment of patients with metastatic melanoma underscoring that galectin 3 or its marker Gal3BP (as well as endostatin) could be part of a panel of biomarkers that predicts the outcome for immunotherapy in melanoma. Our data suggest endostatin and Gal3BP as potential prognostic biomarkers for ipilimumab in MM.…”
Section: Discussionmentioning
confidence: 99%
“…Heart disease acute heart failure plasma level combination with natriuretic peptide [62] acute heart failure plasma level promising prognostic marker [63] chronic heart failure plasma level useful in HF patients with preserved LVEF [64] chronic heart failure myocardial and plasma level not associated with histology [65] acute myocardial infarction serum level no definite relationship with ventricular remodeling [66] Nervous system diseases myelin degeneration tissues activation of the phagocytosis of degenerated myelin [42] intracerebral hemorrhage plasma level prognostic predictor [67] subarachnoid hemorrhage plasma level prognostic predictor [68] global brain ischemia cerebrospinal fluid prognostic marker and inflammatory mediator [69] Renal disease CKD plasma level associated with progression of CKD [25] SLE nephritis serum and biopsy specimens associated with SLE patients, particularly in SLE nephritis [70] Liver disease liver fibrosis serum Gal-3 related binding protein assessing liver fibrosis [71] Connective tissue diseases rheumatoid arthritis serum level increased in early rheumatoid arthritis [72] SLE serum anti-Gal-3 antibody a key role in SLE skin lesions [73] systemic sclerosis serum level predictor of mortality [74] Neoplasms colorectal cancer serum and tissues related to tumor progression [52] breast cancer human cell lines important factor for treatment [75] non-small cell lung cancer tumor expression promotion of invasion and metastasis [76] lung and prostate cancers tumor expression therapeutic target of tumor immunity [77] cervical cancer tumor expression targets of multifunctional cancer treatment [78] thyroid cancer tumor expression diagnostic marker [79]…”
Section: Diseasesmentioning
confidence: 99%
“…Galectins have already been shown to be proteins involved in controlling immune responses in a broad range of diseases (28,38). Most reports on cancer have concentrated on Gal-1 and its effect on immune escape, but it must be emphasized that different galectin members can have different and sometimes opposite effects on T cell behavior (20).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the downregulation of full-length Gal-3 observed in patients apparently matches neither with the definition of Gal-3 as a marker of PCa tumor cell aggressiveness nor with poor marker prognosis for PCa patients (30)(31)(32). However, because Gal-3 controls the functions of a variety of antitumor immune cells (33)(34)(35)(36)(37)(38), we decided to further investigate its role in antitumor immune responses. With the goal to transfer our results to clinics, we paid special attention to conditions where a chemotherapy treatment is associated with vaccination since results from clinical trials have shown that Docetaxel-based chemotherapy could promote the effectiveness of immunotherapy in a variety of cancers (39)(40)(41)(42)(43)(44) as well as in PCa patients (45)(46).…”
Section: Introductionmentioning
confidence: 95%